Effektifitas Larutan Alkohol yang Berulang Kali Dipakai dalam Daya Hambat Bakteri Streptococcus mutans - Ahmad Rizan Aprianda Silakhuddin; Diyah Fatmasari (Poltekkes Kemenkes Semarang, 2015)
Alcohol can be used to decontaminate instrument before washing, as the instruments had been contaminated by million of bacteria from oral cavity. One of the bacteria is Streptococcus mutans. Alcohol mostly used as disinfectant liquid in health services. Based on observation, some hospitals used repeatly used alcohol to soak the instruments before washing. Aims of this research is to know affectivity of repeatly used alcohol towards inhibition of Bacteria Streptococcus mutans. Research design was experimental with quasy experimental laboratory as reseach approach. Samples was 1 ml bacteria Streptococcus Mutans and alcohol 70%, repeatly used alcohol 70% used for 1 day and 5 days. The instruments was soaked on alcohol 70% and repetaly used alcohol for 1 and 5 days. Results shown that alcohol 70% has inhibition zone 4,15 mm (good), repeatly used alcohol 70% for 1 day has inhibition zone 3,88 mm (good) and repeatly used alcohol 70% for 5 days has inhibition zone 2,55 mm (weak). Based on Anova test with significance of 0,02, we conclude that alcohol 70% was more effective than repeatly used alcohol 70% for 1 and 5 days.